2015
DOI: 10.1021/acscatal.5b00723
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of Isopropanol Conversion on Alumina Catalysts: Location of Active Sites for Alkene/Ether Production

Abstract: Alcohol dehydration is of prominent relevance in the context of biomass conversion. This reaction can be efficiently catalyzed by alumina surfaces, but the nature of active sites, the mechanisms involved, and the key parameters to tune both the activity and the alkene/ether selectivity remain a matter of debate. In the present paper, isopropanol dehydration to propene and diisopropylether over γ-alumina, δ-alumina, and sodium-poisoned γ-alumina was investigated through a combined experimental and theoretical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 72 publications
10
107
1
1
Order By: Relevance
“…The ASA supercell contains about 220 atoms and required a 1×1×2 k‐points grid. Transition states were calculated using CI‐NEB, and thermodynamic corrections were performed from vibrational calculations …”
Section: Figurementioning
confidence: 99%
“…The ASA supercell contains about 220 atoms and required a 1×1×2 k‐points grid. Transition states were calculated using CI‐NEB, and thermodynamic corrections were performed from vibrational calculations …”
Section: Figurementioning
confidence: 99%
“…Furthermore, it can be seen that the addition of ruthenium Both supports present very low isopropanol conversion (X IPA ), evidencing the low surface acidity of these supports. It can be seen that the propylene and acetone products are in similar proportions, indicating the presence of weak Lewis acid sites and strong Lewis basics sites [26]. Table 4 shows the result of characterization of ruthenium catalysts (fresh and after reaction).…”
Section: Resultsmentioning
confidence: 99%
“…The nearly five-fold variation (0.9-4.7 × 10 −4 mol g −1 ) in the amount of penta-coordinated Al 3+ ions on thermally treated γ-Al 2 O 3 samples at temperatures from 773 to 1373 K from the report by Hu et al 60 mentioned above supports this conclusion. Larmier et al 56 also suggested that the observed lower 2-propanol conversion rate on δ-Al 2 O 3 compared to γ-Al 2 O 3 at 473 K is a consequence of a different ratio of (100)/(110) surface facets. The results presented in Tables 1-3 show that α-Al 2 O 3 has a lower ethene formation rate constant normalized per surface area compared to γ-and η-Al 2 O 3 demonstrating a lower surface density of ethene formation sites on α-Al 2 O 3 compared to high-surface area alumina polymorphs tested in this report.…”
Section: View Article Onlinementioning
confidence: 99%
“…Knözinger and Scheglila 29 proposed an E2-type mechanism for mono-alcohol dehydration on γ-Al 2 O 3 involving concerted cleavage of the C β -H and C-OH bond and recent DFT calculations have shown lower barriers for an E2-type mechanism for Lewis-acid catalyzed mono-alcohol dehydration. 37,38,[40][41][42][43]54,56 Based on these reports, we consider an E2-type mechanism for ethene formation; however, we note that independent of the detailed mechanistic pathways, the rate expression shown in eqn (1) rigorously describes the measured kinetics of mono-ethanol dehydration at 573 K on α-, γ-, and η-Al 2 O 3 .…”
Section: Kinetics Mechanism and Site Densities Of Ethanol Dehydratimentioning
confidence: 99%
See 1 more Smart Citation